Tube-jack testing for irregular masonry walls: first studies - Ramos, Luís F. (2010)
One of the most well-known non-destructive methods for inspection and diagnosis in historical masonry walls is the flat-jack testing. Although it gives qualitative and valuable results about the local stress level and the deformability of the masonry material, when testing on irregular masonry walls, or walls with larger stone units, experimental and practical problems might occur, leading to inaccurate or useless results. In addition, the testing apparatus is labor, with difficulties in sawing task. Another limitation is the difficulty to test multi-leaves walls. To overturn these problems and to achieve more reliable information, an enhanced type of jacks is proposed in the paper. The new testing system consists of tube-jacks instead of the usual flat-jacks. As part of the preliminary research, analyses with FE models to simulate the differences between the conventional and the enhanced method are presented in the paper. The advantages and disadvantages of both methods are discussed and further research steps are presented.